Achieving the Paris Climate Agreement Goals 2019
DOI: 10.1007/978-3-030-05843-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Just Transition: Employment Projections for the 2.0 °C and 1.5 °C Scenarios

Abstract: This section provides the input data for two different employment development calculation methods: The quantitative analysis, which looks into the overall number of jobs in renewable and fossil fuel industries and the occupational analysis which looks into specific job categories required for the solar and wind sector as well as the oil, gas, and coal industry. Results are given with various figures and tables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
0
15
1
Order By: Relevance
“…Additionally, left and green politicians, along with environmentalists, are interested in understanding the scale and scope of potential renewable energy jobs under a ''green economy.'' 3,7,[13][14][15][16][17][18][19] There are three main strands of literature that have examined potential job shifts. The first has investigated the short-term and economy-wide job impacts of climate-policy-driven energy transitions at the regional 20 and global levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, left and green politicians, along with environmentalists, are interested in understanding the scale and scope of potential renewable energy jobs under a ''green economy.'' 3,7,[13][14][15][16][17][18][19] There are three main strands of literature that have examined potential job shifts. The first has investigated the short-term and economy-wide job impacts of climate-policy-driven energy transitions at the regional 20 and global levels.…”
Section: Introductionmentioning
confidence: 99%
“…The second strand combines estimates of energy sector jobs from input-output models (the Jobs and Economic Development Impact [JEDI] model) with future scenarios of 100% renewable energy systems to estimate direct, indirect, and induced jobs in 2050. 23,24 Finally, the third strand looks at the specific energy sector job impacts of climate policies 13,[15][16][17][25][26][27][28][29][30] using energy systems models to analyze changes in energy jobs, between energy technologies such as coal and solar; job categories such as coal mining and solar manufacturing; and regions under various scenarios. This third type of analysis is important in climate policy debates because empirical and historical analyses have shown that some types of energy workers, such as coal miners or oil extraction workers, exert greater political influence because of their ability to physically control the flow of fuel, due to their higher unionization rates and their iconic status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In very simple terms: it is not only fossil fuels or large-scale systems such as hydroelectricity that can generate their own injustices; solar energy, nuclear power, smart meters and EVs can erode justice principles or create justice concerns as well. Dominish et al (2019) as well as Jenkins et al (2018), Xu and Chen (2019), and Heffron and McCauley (2018), remind us that low-carbon transitions are not merely technical tasks, but socially, politically, and culturally challenging processes that must be managed in fairer and more equitable ways. In line with this body of work, we seek to identify and reveal some of the ethical or moral dilemmas low-carbon transitions raise.…”
Section: Introductionmentioning
confidence: 99%